Student’s Engagement in English Classroom with Hybrid Learning Environment - Syahriyanti; Weda , Sukardi; Iskandar; Fitrah , Andi Muh. (Corolla International Conference, 2025)
The present study seeks to (1) examine the influence of a hybrid learning environment on students’ engagement in learning English, (2) investigate students’ perceptions of differences in their level of engagement between fully online and hybrid classes, and (3) identify the factors and challenges within hybrid learning that shape student engagement in comparison with online-only learning. The research was conducted at Junior High School in Makassar. An autoethnographic approach was employed within a qualitative research design. Cluster random sampling was utilized to select the participants, comprising nineteen students and one English teacher who had experienced both online-only and hybrid modes of instruction. Data were collected through interviews, classroom observations, and documentation. Thematic analysis was applied to analyze the data. The findings reveal that (1) the hybrid learning environment exerts a positive influence on students’ engagement in learning English, (2) students perceive clear differences in their engagement between online and hybrid classes, and (3) several factors and challenges inherent in hybrid learning affect students’ engagement when compared with online-only classes.